MANAJEMEN TATA RUANG PERPUSTAKAAN SMK NEGERI 1 PONTIANAK - Suci Putri; Sisilya Saman Madeten (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractSpatial planning in the library becomes an important part and can affect the performance of librarians and the comfort of visitors. This study discusses the spatial management and obstacles faced in the management of the SMKN 1 Pontianak library. This study aims to describe the management implemented by the school library and the obstacles faced by the librarians in managing the spatial of the library. The study was conducted using the qualitative method in the form of descriptive research. The data collection techniques used were interviews, observation, and documentation. Four informants took part in the interviews. The findings show that the school library conducted spatial planning, which is still simple. There is no specific room for librarians to manage the book collection. The library has not implemented spatial management; Thus, it influenced the librarians’ activities and the visitors’ convenience. The difficulties faced in conducting spatial management were the human resources that lack knowledge in spatial management and the limited library area. Keywords: Management, Spatial, School Library